The role of media education in enhancing recipient awareness A survey study on a sample of students from the Department of Media and Communication at King Khalid University The period from January 2022 AD - January 2023 AD - Ali, Hagir Abdalla Gadalla (Journal of Humanities & Social Sciences, 2024)
The study aims to enhance the role of media education to strengthen positive values and modify or change negative values. It aims to determine the extent of the integration of media and education in enhancing media education for the recipient. It also aims to know the skills required for the recipient to become aware of media education. It also aims to develop the recipient’s awareness to evaluate media messages. The study used a media survey approach to reach results that support the direction of the study. The study tool was a questionnaire that was distributed to a deliberate sample of (51) individuals. The study concluded with a number of results, the most important of which are: Most of the sample members believe that media education achieves the building of a healthy human personality at a rate of (78.5%), and that media education achieves an individual’s awareness of his rights and duties at a rate of (92.2%). The integration of media and education contributes to the formation of open-minded, democratic individuals and societies (64.7%). The integration of media and education contributes to preparing media professionals to perform the educational process at a rate of (84.3%). Media education enables the recipient to understand the background and objectives of the media message at a rate of (72.5%). The study also reached a number of recommendations, the most important of which are: the need for media education to give greater importance to the issue of awareness of democracy and openness, because societies still need more democracy, so that they can practice their activities in a way that is open to all options. Then consciously choose the appropriate option, focus on preparing media professionals to perform the educational process, and prepare an active recipient to participate in producing useful media content. The researcher also recommends the necessity of integrating the roles of media and education to give the recipient a conscious understanding of media culture.